Understory Plant Species Diversity in Pine Tree Stands in Bukit Cadika Pine Forest Bangkinang - Shobby, Afiyah; Yoza, Defri; Pebriandi, Pebriandi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Bukit Cadika Pine Forest Bangkinang is one of the pine forests in Bangkinang Riau. Pine is a type of tree that is classified as a fast-growing type and does not require special requirements in its planting, so pine can spread naturally to areas south of the equator. The existence of understory plants can also function as soil protectors from rain grains and surface flow and play a role in increasing organic matter in the soil. This study aims to determine the diversity of understory plant species in Bukit Cadika Pine Forest stands Bangkinang. Data collection methods and lower plant samples were carried out in pine stands through direct field observations using the path/transect method. The placement of paths in this study was carried out using purposive sampling technique with a total of 5 paths made and a distance of 1 m between paths with a path length of 100 m. The data obtained in the field were analyzed using the data collection method. Data obtained in the field were analyzed using the Shannon-Wiener diversity index, species evenness index and important value index. The conclusion in this study found as many as 13 species with a total of 201 individuals and 12 families that were successfully identified and the species diversity index in Bukit Cadika pine forest stands amounted to 2.18 which is included in the moderate category.